Bibliographic Supplement with Annotation, on Disability, Deafness and Religious Belief and Practice in Middle Eastern, South Asian and East Asian Histories and Cultures - Miles, M. (Journal of religion, disability & health, 2007)
This is a supplement of about 150 items to the earlier bibliography (180 items) published in the Journal of Religion, Disability & Health(2002) vol. 6 (2/3) pp. 149-204. It lists and annotates materials (often in translation, sometimes with commentary) pertinent to disability, deafness and religious belief and practice in the histories and cultural traditions of the Middle East, South Asia and East Asia.